Career perspectives and reality for pedagogy graduates in 2012 using the example of the students of the University of Wrocław majoring in rehabilitation - Małgorzata Kozłowska (Journal of Education Culture and Society, 2012)
The subject of the article is the issue of career development of students that have graduated from 5-years pedagogy studies with the master diploma at the University of Wrocław in 2011. The article is supposed to confront the assumed profi le of the pedagogy graduates placed on the university website with the reality on the job market. The essential assumption of the article is the attempt to receive the most possible comprehensive picture of the former students’ career perspectives and the reality they encounter on the basis of their relation, not only the statistics available. The article will also cover the analysis of the qualifications gained during the studies but also all other factors that turned out to be helpful to find an employment consistent with their expectations.